Factors Influencing Motor Vehicle Tax Compliance in Sukabumi Regency - Setiawan, Angga Permana; Hambani, Susy; Aziz, Ayi Jamaludin (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This research aims to examine the influence of tax knowledge, taxpayer awareness, taxpayer income, and tax sanctions on motor vehicle taxpayer compliance in Sukabumi Regency. This research uses quantitative methods with surveys as a data collection technique. The population in this study includes all taxpayer vehicles registered at the PPPD Sukabumi 1 Cibadak Regency Area, totaling 369,165 taxpayers. A sample of 100 motor vehicle taxpayers was selected using a probability sampling technique with a simple random sampling method. The research results show that tax knowledge, taxpayer awareness, taxpayer income, and tax sanctions simultaneously have a positive influence on motor vehicle taxpayer compliance. Partially, tax knowledge and taxpayer awareness do not have a positive influence on motor vehicle taxpayer compliance, while taxpayer income and tax sanctions have a positive influence on motor vehicle taxpayer compliance.